Perfluoroalkyl substances (PFASs) in white whales (Delphinapterus leucas) from Svalbard – A comparison of concentrations in plasma sampled 15 years apart. (August 2020) - Villanger, Gro D.; Kovacs, Kit M.; Lydersen, Christian; Haug, Line S.; Sabaredzovic, Azemira; Jenssen, Bjørn M.; Routti, Heli
Abstract: The objective of the present study was to investigate recent concentrations of perfluoroalkyl substances (PFASs) in white whales ( Delphinapterus leucas ) from Svalbard and compare them to concentrations found in white whales sampled from that same area 15 years ago. Plasma collected from live-captured white whales from two time periods (2013–2014, n = 9, and 1996–2001, n = 11) were analysed for 19 different PFASs. The 11 PFASs detected included seven C8 –C14 perfluoroalkyl carboxylates (PFCAs) and three C6 –C8 perfluoroalkyl sulfonates (PFSAs) as well as perfluorooctane sulfonamide (FOSA). Recent plasma concentrations (2013–2014) of the dominant PFAS in white whales, perfluorooctane sulfonate (PFOS; geometric mean = 22.8 ng/mL), was close to an order of magnitude lower than reported in polar bears ( Ursus maritimus ) from Svalbard. PFOS concentrations in white whales were about half the concentrations in harbour ( Phoca vitulina ) and ringed ( Pusa hispida ) seals, similar to hooded seals ( Cystophora cristata ) and higher than in walruses ( Odobenus rosmarus ) from that same area. From 1996 to 2001 to 2013–2014, plasma concentrations of PFOS decreased by 44%, whereas four C9-12 PFCAs and total PFCAs increased by 35–141%. These results follow a similar trend to what has been reported in other studies of Arctic marine mammals from Svalbard. The most dramatic change has been the decline of PFOS concentrations since 2000, corresponding to the production phase-out of PFOS and related compounds in many countries around the year 2000 and a global restriction on these substances in 2009. Still, the continued dominance of PFOS in white whales, and increasing concentration trends for several PFCAs, even though exposure is relatively low, calls for continued monitoring of concentrations of both PFCAs and PFSAs and investigation of biological effects. Graphical abstract: Image 1 Highlights: 19 PFASs were analysed in plasma from Svalbard white whales sampled 15 yrs apart. PFOS dominated in both 1996–2001 and 2013–2014 among the 11 detected PFASs. PFOS decreased 44% over the last 1.5 decades and C9-12 PFCAs increased by 35–141%. The main time trends are similar to other marine mammal studies from Svalbard. Abstract : Short quote: Perfluoroalkyl substances have been measured in white whales from Svalbard sampled 15 years apart. PFOS has decreased by 44% while some of the persistent C9-12 PFCAs have increased by 35–141%.